Predictors of silent hypoxia in hospitalized patients with COVID-19 in Japan. Issue 10 (October 2022) - Hayakawa, Kayoko; Morioka, Shinichiro; Asai, Yusuke; Tsuzuki, Shinya; Yamada, Gen; Suzuki, Setsuko; Matsunaga, Nobuaki; Ohmagari, Norio
Abstract: Introduction: Silent hypoxia (SH) is common in patients with coronavirus disease (COVID-19) in Japan and other countries. Early identification of SH is important as more treatment options for COVID-19 have become available. This study aimed to identify predictors of SH using a nationwide COVID-19 registry of hospitalized patients. Methods: Adult patients who were admitted to hospital with COVID-19 between January 2020 and June 2021 and who were hypoxic on admission (SpO2 : 70–93%), not transferred from another facility, and who did not have disturbance of consciousness, confusion, or dementia, were included. SH was defined as hypoxia in the absence of shortness of breath/dyspnea upon admission. Predictors of SH were identified using univariable and multivariable logistic regression. Results: The study included 1904 patients, of whom 990 (52%) satisfied the criteria for SH. Compared to patients without SH, patients with SH were older, more likely to be female, and had a slightly higher SpO2 on admission. Compared to patients without SH, patients with SH had a lower prevalence of chronic lung disease (CLD) other than chronic obstructive pulmonary disease (COPD), asthma, and obesity. Multivariable analysis revealed that the independent predictors of SH were older age, a shorter interval from symptom onset to admission, higher SpO2, and an absence of CLD or COPD. Conclusions: The absence of underlying lung disease and older age were important predictors of SH. The results of this study, which is the largest such study reported to date in Japan, may help clarify the mechanism of SH.